A knowledge-based primary care approach to increase breast screening attendance. (6th February 2009) - Baskaran, V.; Bali, R.K.; Arochena, H.; Naguib, R.N.G.; Wheaton, M.; Wallis, M.; Wickramasinghe, Nilmini
The static rate of breast screening attendance in the UK has been of concern in the fight against breast cancer mortality. This paper highlights how primary care can play a vital role in addressing this issue. Knowledge created through prediction mechanisms and sharing them with care deliverers forms the core of this discussion. Knowledge-based alerts are employed to initiate interventions to increase the breast screening attendance. This paper highlights the various factors that are to be considered while deploying such initiatives in primary care setting and validates them through a questionnaire-based survey.